Protected areas and biodiversity conservation in India. (September 2019) - Ghosh-Harihar, Mousumi; An, Ruby; Athreya, Ramana; Borthakur, Udayan; Chanchani, Pranav; Chetry, Dilip; Datta, Aparajita; Harihar, Abishek; Karanth, Krithi K.; Mariyam, Dincy; Mohan, Dhananjai; Onial, Malvika; et al.
Abstract: Three well-supported generalizations in conservation biology are that developing tropical countries will experience the greatest biodiversity declines in the near future, they are some of the least studied areas in the world, and in these regions especially, protection requires local community support. We assess these generalizations in an evaluation of protected areas in India. The 5% of India officially protected covers most ecoregions and protected areas have been an important reason why India has suffered no documented species extinctions in the past 70 years. India has strong legislation favouring conservation, government investment focused on 50 Tiger Reserves, and government compensation schemes that facilitate local support, all of which brighten future prospects. However, many protected areas are too small to maintain a full complement of species, making connectivity and species use of buffer zones a crucial issue. Conservation success and challenges vary across regions according to their development status. In less developed areas, notably the biodiverse northeast Himalaya, protected areas maintaining the highest biodiversity result from locally-focused efforts by dedicated individuals. Across India, we demonstrate considerable opportunities to increase local income through ecotourism. Our evaluation confirms a lack of data, increasing threats, and the importance of local support. Research on biodiversity in buffer zones, development of long-term monitoring schemes, and assessment of cash and conservation benefits from tourism are in particular need. For policy makers, two main goals should be the development of monitoring plans for 'eco-sensitive zones' around protected areas, and a strong emphasis on preserving established protected areas. Highlights: We review the history, status and prospects of protected areas in India Strong legislation, government investment and local support have aided conservation Data on protected area status is short. Key threats vary by region, from poaching in remote northeast to development projects in peninsular India Research needs include monitoring and evaluating conservation and ecotourism value of buffer zones around protected areas